2010
DOI: 10.1016/j.jvs.2009.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured brachial artery aneurysm in a patient with type 1 neurofibromatosis

Abstract: Vascular lesions associated with neurofibromatosis type 1 (NF1) are rare but can lead to catastrophic complications if disrupted. Ruptured aneurysms in NF1 patients are difficult to treat surgically because of vascular wall fragility. We describe a female NF1 patient with a ruptured aneurysm of her brachial artery. This is the first published case of successful reconstruction of a ruptured brachial aneurysm associated with NF1, using a saphenous vein graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Although some authors successfully recreated a vascular conduit using vein graft, many others reported failed reconstruction or adopted salvage procedures such as simple ligation and resection with high mortality and morbidity. 8,10,14,15 Emori et al 10 reported a case series of three ruptured aneurysms of the brachial artery that developed in patients with NF1 treated by surgical revascularization. Unfortunately, the outcome was extremely poor with two deaths and one requiring transhumeral amputation due to unsuccessful repair of the brachial artery.…”
Section: Case Reportmentioning
confidence: 99%
See 4 more Smart Citations
“…Although some authors successfully recreated a vascular conduit using vein graft, many others reported failed reconstruction or adopted salvage procedures such as simple ligation and resection with high mortality and morbidity. 8,10,14,15 Emori et al 10 reported a case series of three ruptured aneurysms of the brachial artery that developed in patients with NF1 treated by surgical revascularization. Unfortunately, the outcome was extremely poor with two deaths and one requiring transhumeral amputation due to unsuccessful repair of the brachial artery.…”
Section: Case Reportmentioning
confidence: 99%
“…Consequently, because of the extreme vessel wall fragility and the difficulties in obtaining haemostasis, surgical treatment of ruptured aneurysms in NF1 is technically demanding. 10 As a result, very little is known about the natural history of the peripheral arterial aneurysms associated with NF1 and the optimal management in such cases. 2 Some investigators recommend that a NF1 related aneurysm might be better treated by an endovascular approach (including stenting or embolization) or a hybrid procedure, rather than by surgery alone, providing the distal circulation is preserved.…”
Section: Case Reportmentioning
confidence: 99%
See 3 more Smart Citations